Does case-based blended-learning expedite the transfer of declarative knowledge to procedural knowledge in practice? - Turk, Bela (BMC Med Educ, 2019)
BACKGROUND: Case-Based Learning (CBL) has seen widespread implementation in undergraduate education since the early 1920s. Ample data has shown CBL to be an enjoyable and motivational didactic tool, and effective in assisting the expansion of declarative and procedural knowledge in academia. Although a plethora of studies apply multiple choice questions (MCQs) in their investigation, few studies measure CBL or case-based blended learning (CBBL)-mediated changes in students’ procedural knowledge in practice or employ comparison or control groups in isolating causal relationships. METHODS: Utilizing the flexibilities of an e-learning platform, a CBBL framework consisting of a) anonymized patient cases, b) case-related textbook material and online e-CBL modules, and c) simulated patient (SP) contact seminars, was developed and implemented in multiple medical fields for undergraduate medical education. Additionally, other fields saw a solo implementation of e-CBL in the same format. E- cases were constructed according to the criteria of Bloom’s taxonomy. In this study, Objective Structured Clinical Examination (OSCE) results from 1886 medical students were analyzed in total, stratified into the following groups: medical students in 2013 (n = 619) before CBBL implementation, and after CBBL implementation in 2015 (n = 624) and 2016 (n = 643). RESULTS: A significant improvement (adjusted p = .002) of the mean OSCE score by 1.02 points was seen between 2013 and 2015 (min = 0, max = 25). CONCLUSION: E-Case-Based Learning is an effective tool in improving performance outcomes and may provide a sustainable learning platform for many fields of medicine in future.